Development Of Digital Comic Learning Media Based on Local Wisdom in Pancasila And Citizenship Education Subjects - Alfanda, Noviyasti; Jamaludin, Ujang; Bahrudin, Febrian Alwan (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2024)
Education is an attempt made to facilitate understanding, awareness, and development of knowledge, analytical skills, and effective skills through various learning media. In this research, problems existed in the form of a lack of innovation in the use of learning media and difficulty for students to understand the material. Thus, there was a need for innovative media for learning, like digital comics. However, digital comic media had drawbacks that must be improved through the development stage. Hence, this research aimed to create innovation by developing media for learning in the form of corresponding digital comics. The method used was RD (Research and Development) with Thiagarajan's 4D model, consisting of Define, Design, Development, and Dissemination. The findings showed: "Highly Feasible" by media validators with 84.76%, "Feasible" results from material experts with 71%, and "Highly Feasible" results by practicing material experts with 92%. Furthermore, students' responses to conducted by limited trials to seventh grade students of SMP Negeri 2 Anyer obtained "Excellent" results with 85.04% and in the field test to seventh grade students of SMP Negeri 2 Anyer obtained "Excellent" results with 84.83%. Accordingly, the findings were considered significantly important to create innovation in the use of media for learning, and it is possible to deduce that digital comic learning media based on local wisdom of Pancasila and education citizenship subject.